Application of environmental assessment methods for building materials when comparing various aspects of environmental impact - Kulik, M.; Ishchenko, S.; Chupryna, L. (Ways to Improve Construction Efficiency, 2019)
This article discusses the methods of environmental assessment of building materials in terms of their hygienic safety, identifies these safety criteria and characteristics to assess the impact of building materials on human health. On their basis, we developed ecological ways to improve the sanitary and hygienic properties of finishing materials.